2017
DOI: 10.1111/cid.12506
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy for reconstruction of alveolar cleft and trauma defects in adults: A randomized controlled, clinical trial

Abstract: The ability of stem cells to treat large alveolar defects is safe, yet, their ability to completely reconstitute large alveolar defects is limited. This approach requires further optimization to meet the outcomes seen using current methods to treat large defects, particularly those resultant of cleft palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 33 publications
2
93
0
3
Order By: Relevance
“…The authors hypothesize that these accessory cells may serve to enhance tissue regeneration by promoting vascularization and modulating the inflammatory response in the regenerating tissues (Dennis et al., ). However, no significant differences in NBF were observed when comparing TRC‐scaffold constructs with scaffolds alone (Hernandez Alfero et al., ; Kaigler et al., , ) or AB (Bajestan et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…The authors hypothesize that these accessory cells may serve to enhance tissue regeneration by promoting vascularization and modulating the inflammatory response in the regenerating tissues (Dennis et al., ). However, no significant differences in NBF were observed when comparing TRC‐scaffold constructs with scaffolds alone (Hernandez Alfero et al., ; Kaigler et al., , ) or AB (Bajestan et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…These results suggest successful clinical application in regenerating periodontal tissue, including bone tissue [41]. In alveolar cleft surgery, several clinical trials, mainly case reports, suggest promising results with the application of BMSCs, but complete reconstruction (bone fill) of extensive cleft defects has not been demonstrated [42,43]. In contrast, Hermund et al [44] showed no difference in bone density and height between a control group (graft composed of a mixture of bovine bone substitute and autologous bone particles) and a test group (same scaffold, supplemented with BMSCs that were retrieved from the tuberosity and cultivated in vitro) after maxillary sinus floor elevation.…”
Section: Sources Of Stem Cellsmentioning
confidence: 99%
“…The two studies evaluated in this systematic review produced equivocal results with one reporting improved bone formation after implantation of bone marrow stromal stem cells (Dallari et al., ) and one report failing to find any such effect (Liebergall et al., ). A recent study investigating the use of bone marrow stem cells for the regeneration of alveolar cleft and trauma in adults found that while the use of these cells is safe, their ability to facilitate complete regeneration of large alveolar defects is limited (Bajestan et al., ). Most recently, significant regeneration (in both horizontal and vertical dimensions) for severe mandibular resorption has been reported when bone marrow stromal stem cells were used in conjunction with biphasic calcium phosphate scaffolds and titanium‐reinforced membranes (Gjerde et al., ).…”
Section: Mesenchymal Stem Cells and Bone Regenerationmentioning
confidence: 99%